Pembuatan Nugget Tempe Dalam Pemenuhan Gizi Balita Cegah Stunting - Tengku Hartian; Siska Mulyani; Mustika Hana Harahap; Andriani Andriani; Yessi Azwar; Donny Hendra (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Good nutrition is an important foundation for a child to grow and develop optimally, especially children who grow and develop in vulnerable environments. The results of the 2021 Nutritional Status survey show that 1:4 Indonesian children experience stunting and 1:10 children experience malnutrition. Prevention of stunting must be as early as possible, starting from portions of the plate with balanced nutritional content. Tempeh is a fermented product made from soybeans, the price is quite cheap, tempeh is also the best source of energy and protein, tempeh contains prebiotics which are good for the intestines, low in sodium and carbohydrates. 84 grams of tempeh contains 162 calories, 15 grams of protein, 9 grams of carbohydrates, 9 milligrams of sodium and many others. Efforts can be made to increase the knowledge and skills of cadre mothers and mothers of toddlers by conducting counseling, demonstrations and simulating tempe food. This dedication has a positive effect on knowledge, skills and ideas in making a variety of healthy snacks. The aim of this community service is so that mothers of babies and toddlers know and understand that tempeh food can be processed into various healthy snack ingredients to prevent stunting. The method of implementing activities in general includes the stages of introduction, counseling, demonstration and evaluation. It is hoped that in the future, cadre mothers and the community, especially mothers who have babies and toddlers in RW03 RT02, Kualu Village, Tambang Kampar District, will be more creative in making preparations made from tempeh that are rich in nutrients in an effort to prevent stunting and more often seek the latest information about nutrition in the reproductive cycle.